Enhancing surgical safety and efficiency: systematic review and single-arm meta-analysis of surgical data recorders - Siegel, Niels Wolfgang; Rotärmel, André; Polychronidis, Georgios; Salg, Gabriel Alexander; Klotz, Rosa; Probst, Pascal; Pausch, Thomas (Journal of medical internet research, 2025)
Background: Recently surgical data recorders comparable to flight data recorders also known as black boxes in the aviation industry have been developed to improve patient safety and performance in surgery. These devices allow for unique insights in the operating room by providing new data capture capabilities. No systematic review has been carried out to evaluate the areas of application of surgical data recorders to date. Objective: This systematic review and single-arm meta-analysis aimed to assess which aspects of the operating theatre environment surgical data recorders are used for. And to make a preliminary assessment of the quantifiable data that can be collected compared to traditional collection methods. Methods: The systematic review followed the PRISMA guidelines. Medline, Embase and Web of Science databases were lastly systematically searched for papers that focused on a clinical use case for surgical data recorders on February 10th 2025. Not relevant papers in particular papers focusing on implementation of surgical data recorders were excluded. Title, abstract and full-text screening were completed to identify relevant articles. The included studies were analyzed descriptively using data extraction forms. Where possible, quantifiable data was also analyzed. Risk of bias was assessed using the ROBINS-E tool. Results: 70 studies were screened and a total of 17 studies were included. Ten of the 17 studies had a low overall risk of bias; however, confounding, selection bias, small sample sizes, short study periods, and potential Hawthorne effects were notable limitations. Only 2 studies were assessed to have publication bias. Use cases could be grouped into four categories: economic, safety, behaviour in the OR and technical skill assessment. A single-arm meta-analysis focusing on adverse events and distractions in the operating theatre could be conducted, demonstrating accurate reporting of distractions in line with the existing literature. Conclusions: Surgical data recorders provide an unobstructed view of various aspects of the operating theatre. Most published papers present preliminary studies on surgical data recorders, indicating the potential for further, larger-scale studies with enhanced methodological quality.